Krisis Perencanaan Transportasi Kota - Harun al-Rasyid S Lubis; Rudy Hermawan Karsaman (The Institute for Research and Community Services, Institut Teknologi Bandung, 1997)
In Indonesia, the study on the correlation between land-use and transportation was started 21 cyears ago following similiar studies conducted by developed countries 43 years ago. The main purpose of these studies was to prepare an efficient transportation plan for a city or region in order to facilitate the increase in the traffic as the result of the growth of social-economic activities in the city in the future Due to inconsistency between plan and reality in the implementation phase, in the developed countries critiques on the failures of these studies emerged in the middle of 1970